Relationship Between the Practice of Tai Chi for More Than 6 Months With Mental Health and Brain in University Students: An Exploratory Study - Li, Xiaoyuan; Geng, Jintao; Du, Xiaoyu; Si, Hongyu; Wang, Zhenlong (Frontiers in Human Neuroscience, 2022)
To study whether Tai Chi (TC) practice can improve the brain connectivity of prefrontal lobe of college students, the positive psychological capital questionnaires and resting EEG signals were acquired from 50 college students including 25 TC practitioners and 25 demographically matched TC healthy controls. The results showed that the score of positive psychological capital questionnaire of TC group was significantly higher than that of the control group, and the node degree of frontal lobe and temporal lobe of both groups was positively correlated with the score of positive psychological capital questionnaire. In addition, the response time of TC group under auditory stimulation was significantly shorter than that of the control group, and there was a significant positive correlation between response time and its characteristic path length, and a significant negative correlation with global efficiency. Meanwhile, during the selected range of sparsity, the difference of global network parameters between two groups is significant in alpha band. Under all single sparsity, the clustering coefficient, global efficiency and local efficiency of TC group has a higher trend, while the characteristic path length tended to be shorter. In the analysis of the local characteristics of the resting brain functional network, it was found that the node degree of the frontal lobe and temporal lobe of the TC group was higher, and the difference was significant in some nodes. These results all point to the fact that TC practice has a certain impact on specific brain areas of the brain.